2004
DOI: 10.1111/j.1095-8649.2004.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body size, temperature, and salinity on the routine metabolism of larval and juvenile spotted seatrout

Abstract: Routine oxygen consumption rates of young spotted seatrout Cynoscion nebulosus (Sciaenidae) were measured over a range of temperatures (24, 28, 30 and 32 C) and salinities (5, 10, 20, 35 and 45). Larvae and juveniles, 4Á1-39Á5 mm standard length (L S ), ranging several orders of magnitude in dry body mass were used to estimate the mass-metabolism relationship. Oxygen consumption (ml O 2 larva À1 h À1 ) scaled isometrically with body mass for larvae <5Á8 mm L S (phase I, slope ¼ 1Á04) and allometrically therea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 33 publications
2
23
0
2
Order By: Relevance
“…Negative impacts of low salinities on OCRs have also been recorded for larvae of various invertebrate species [37], [42], [43], [44], [45], [77], [78], [79]. Because the gastropod velum has been described as a major respiratory organ for gastropod larvae [72], the decrease in oxygen consumption by C. peruviana larvae would be closely linked to the lack of activity and decreased size of the velum in stressed veligers, considering that a smaller velum implies a smaller surface area available for gas exchange [72].…”
Section: Discussionmentioning
confidence: 92%
“…Negative impacts of low salinities on OCRs have also been recorded for larvae of various invertebrate species [37], [42], [43], [44], [45], [77], [78], [79]. Because the gastropod velum has been described as a major respiratory organ for gastropod larvae [72], the decrease in oxygen consumption by C. peruviana larvae would be closely linked to the lack of activity and decreased size of the velum in stressed veligers, considering that a smaller velum implies a smaller surface area available for gas exchange [72].…”
Section: Discussionmentioning
confidence: 92%
“…Preliminary trials indicated that cold formalin euthanized larvae quickly and minimized any regurgitation or continued digestion of food. The notochord or standard length ( L S ) of each fish was measured under a dissecting microscope, and dry mass ( M D ) calculated from the length‐mass relationship of Wuenschel et al . (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, intra-specific scaling exponents for f H and M O2 have been shown to vary throughout development (e.g. Barrionuevo and Burggren, 1999;Wuenschel et al, 2004;Moran and Wells, 2007), thus precluding extrapolation of scaling exponents to adult fish and highlighting the need to account for ontogeny and maturity when examining M b scaling.…”
Section: Introductionmentioning
confidence: 99%